Underlying the notion of development in the formulation of urban regulations of Villa Gesell (1999–2020) - Julián Stramigioli (ARQUISUR Revista, 2021)
The notion of development has given rise in recent decades to the construction of discourses with which certain public policies are validated and legitimized (or delegitimized). In the urban sphere, this construction takes on a special strength from the preponderance of the production of space as the preferential locus of the reproduction of capital from the world economic restructuring that began in 1970. For this reason, here we will seek to analyze in what form is manifested (or not) this notion in the production of urban regulations of the Villa Gesell Party, taking as case studies the two main instances in which an attempt was made to more or less fully translate into a document a series of intentions related to the urban planning by the municipality, since its creation in 1978.